The relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers aged 0-24 months in the tawiri health center work area - Fajar, Harianti; Saukoly, Dessy Ade (CV. Paperhome Indonesia, 2025)
Background: Mothers who experience poor nutritional status are at risk of giving birth to stunted children. The purpose of this study was to analyze the relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers aged 0-24 months in the Tawiri Health Center work area. Method: This study used a retrospective method to analyze the relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers aged 0-24 months in the Tawiri Health Center work area. Result: The results showed that most mothers experienced poor nutritional status during pregnancy. Mothers with poor nutritional status during pregnancy are at higher risk of giving birth to children who experience stunting. Conclusion: Maternal nutritional status during pregnancy is related to the incidence of stunting. Therefore, it is necessary to conduct socialization of health education about stunting and fulfillment of nutritional needs during pregnancy to health workers at the Tawiri Health Center.